PERANAN KELOMPOK KERJA MADRASAH (KKM) SEBAGAI SKOCI PENINGKATAN MUTU PENDIDIKAN ISLAM - Achmad, Abdul Kholid (J-MPI (Jurnal Manajemen Pendidikan Islam), 2021)
This study aims to determine the role of the Madrasah Working Group (KKM) in accordance with the Decree of the Directorate General of Islamic Religious Education Number 5852 of 2020 concerning Technical Guidelines for the Implementation of the KKM. The research was conducted with a qualitative descriptive case study type approach. The research findings show that the role of KKM can be optimal by using several programs and activities as follows: (1) sharing strategies among madrasah principals on best practices, (2) implementing inter-institutional benchmarking as part of honing, compassion and fostering, (3) making programs periodic collective evaluation (cognitive and psychomotor) to get superior seeds through programs and activities as well as a show-a-force institutional promotion, and (4) fostering and enhancing the professionalism of madrasah principals through programmed KKM on an ongoing basis by referring to the results of the evaluation conducted by the madrasah supervisor. Through KKM, efforts can be made to improve the quality of Islamic education whenever it is carried out programmatically and continuously based on evaluation data.